Equilibrium, kinetic and thermodynamic studies of the adsorption of trypan blue dye by Pseudomonas sp. strain MM02 inactivated biomass - Abubakar, Abdussamad; Manogaran, Motharasan; Yasid, Nur Adeela; Othman, Ahmad Razi; Abd Shukor, Mohd Yunus (Springer Science and Business Media LLC, 2023)
More concerning about dye pollution is that it is being worsened by a lack of adequate treatment. This study optimized the adsorption of Trypan Blue (TB) dye in an aqueous solution using screened bacterial biomass. Among twelve different bacterial isolates screened against TB dye, Pseudomonas sp. strain MM02 showed a high adsorption percentage of 36.5%. The adsorption process was enhanced using one-factor-at-a-time (OFAT) and response surface methodology (RSM) optimization. An adsorption of 59% was achieved through OFAT optimization (TB dye concentration 15 ppm, contact time 20 min, pH 6.5, agitation speed 150 rpm, adsorbent amount 1.10 g and temperature 30 °C), while statistical optimization using RSM resulted in a further increased adsorption of the dye to 61.51% (TB dye concentration 22.27 ppm, adsorbent size 0.32 g, and temperature 34.27 °C). The results of this investigation demonstrated that OFAT and RSM optimization were effective and that they were also appropriate strategies for optimizing the adsorption of TB dye by Pseudomonas sp. strain MM02. Thus, it is possible to achieve the necessary water quality while saving money by using the strain MM02 of Pseudomonas sp. MM02 in a water treatment facility. Changes in free energy of adsorption (ΔGo), enthalpy (ΔHo) and entropy (ΔSo) as well as the activation energy (Ea) were determined. ΔHo, ΔSo and Ea with pH control were −26.5, −230 and 43.5 kJ/mol. The result showed that bacterial cellulose could be employed as an effective sorbent for the removal of direct dye from an aqueous solution and the values of ΔHo, ΔGo and Ea indicate that the adsorption of direct dye onto bacterial cellulose was a physisorption process: ΔGo and ΔHo.